Therapeutic Ultrasound as a Potential Male Dog Contraceptive: Determination of the Most Effective Application Protocol. Issue 5 (2nd July 2015) - Leoci, R; Aiudi, G; Silvestre, F; Lissner, EA; Marino, F; Lacalandra, GM
Contents: Ultrasound is one of the most promising forms of non‐invasive contraception and has been studied in several animal models. The objective of the current investigation was to determine the most practical and effective application protocol for dog sterilization. A total of 100 dogs were divided into five equal groups. Group A received 5‐min applications three times performed at 48‐hr intervals and covering the entire testicular area at frequency of 1 MHz; Group B received 5‐min applications three times performed at 48‐hr intervals over the dorso‐cranial area of the testis at frequency of 3 MHz; Group C received three sequential 5‐min applications (at 5‐min intervals between applications) covering the entire testicular area at frequency of 1 MHz; Group D received 15‐min applications two times performed at 48‐hr intervals and covering the entire testicular area at frequency of 1 MHz. The experimental groups' ultrasound had an intensity of 1.5W/cm 2 . The Control Group had the same procedure as Group A, but with the transducer switched‐off. Dogs were surgically castrated 40 days following the treatment for histological examination. Azoospermia, testicular volume reduction and apparently irreversible testicular damage were achieved by Group A. No effects were noticed in the other groups. Testosterone levels remained within physiological range with all application protocols. A regimen of three applications of ultrasound at 1 MHz, and 1.5 W/cm 2, lasting 5 min with an interval of 48 h was effective as permanent sterilization in the dog without hormonal impact.